Some Aspects of Teaching Academic Essay Writing at Technical University - Данилова, С. В.; Danylova, S. V. (My University, 2009)
It is focused on teaching academic essay writing to students who study English for specific purposes. Academic essay writing is considered to be an effective means of developing students’ critical thinking which deals with exercising different mental activities. It is given а classification of essays and analyzed the structure of a scientific essay
Danylova, S. V. Some Aspects of Teaching Academic Essay Writing at Technical University / S. V. Danylova // Гуманіт. вісн. НУК. – Миколаїв : НУК, 2009. – Вип. 2. – С. 48–55.
Keywords: академічне письмо; есе; види есе; критичне мислення; навички мислення; academic writing; academic essay; kinds of essays; thinking skills